Conceptualizando el Buen Vivir: entre la felicidad y la crítica - Piñeiro Aguiar, Eleder (2016)
Buen Vivir is analyzed in its relationship with two theoretical currents such as those from Western philosophy around the idea of happiness and the colonial theory and criticism of Eurocentric canon of knowledge production. Collecting items from various academic sources, analysis of Good Living in their relationship with the critique of neoliberal - Eurocentric model is proposed, concluding that the idea of building this Andean proposal is part of the global struggle to globalizing capitalist model, exposing the need understand the economic sumac kawsay as a network of political statements, philosophical, moral, generating ruptures regarding the Western canon of thought and development.